KIR content genotypes associate with carriage of hepatitis B surface antigen, e antigen and HBV viral load in Gambians - Yindom, L; Mendy, M; Bodimeade, C; Chambion, C; Aka, P; Whittle, H; Rowland-Jones, S; Walton, R (Public Library of Science, 2017)
Background Hepatocellular carcinoma (HCC) causes over 800,000 deaths worldwide annually, mainly in low income countries, and incidence is rising rapidly in the developed world with the spread of hepatitis B (HBV) and C (HCV) viruses. Natural Killer (NK) cells protect against viral infections and tumours by killing abnormal cells recognised by Killer-cell Immunoglobulin-like Receptors (KIR). Thus genes and haplotypes encoding these receptors may be important in determining both outcome of initial hepatitis infection and subsequent chronic liver disease and tumour formation. HBV is highly prevalent in The Gambia and the commonest cause of liver disease. The Gambia Liver Cancer Study was a matched case-control study conducted between September 1997 and January 2001 where cases with liver disease were identified in three tertiary referral hospitals and matched with out-patient controls with no clinical evidence of liver disease. Methods We typed 15 KIR genes using the polymerase chain reaction with sequence specific primers (PCR-SSP) in 279 adult Gambians, 136 with liver disease (HCC or Cirrhosis) and 143 matched controls. We investigated effects of KIR genotypes and haplotypes on HBV infection and associations with cirrhosis and HCC. Results Homozygosity for KIR group A gene-content haplotype was associated with HBsAg carriage (OR 3.7, 95% CI 1.4–10.0) whilst telomeric A genotype (t-AA) was associated with reduced risk of e antigenaemia (OR 0.2, 95% CI 0.0–0.6) and lower viral loads (mean log viral load 5.2 vs. 6.9, pc = 0.022). One novel telomeric B genotype (t-ABx2) containing KIR3DS1 (which is rare in West Africa) was also linked to e antigenaemia (OR 8.8, 95% CI 1.3–60.5). There were no associations with cirrhosis or HCC. Conclusion Certain KIR profiles may promote clearance of hepatitis B surface antigen whilst others predispose to e antigen carriage and high viral load. Larger studies are necessary to quantify the effects of individual KIR genes, haplotypes and KIR/HLA combinations on long-term viral carriage and risk of liver cancer. KIR status could potentially inform antiviral therapy and identify those at increased risk of complications for enhanced surveillance.